The Influence Of Social Media Marketing And Brand Image On The Decision To Use Products At Asiah Florist Manna Bengkulu Selatan - Lora Nopita Sari; Yun Fitriano; Yudi Irawan Abi (Universitas Dehasen Bengkulu, 2026)
This research uses quantitative research. The analytical method in this study uses Validity Test, Reliability Test, Multiple Linear Regression Analysis, Coefficient of Determination, and hypothesis testing using the t-test. The number of samples studied was 85 customers who came with various orders during the past month at the Asiah Florist Shop, South Bengkulu. The results of the multiple linear regression analysis are the equation: Y = 8.009 + 0.441 X1 + 0.388 X2 + e. This illustrates a positive regression direction, meaning that the social media marketing variables (X1) and brand image (X2) have a positive influence on customer satisfaction (Y) at the Asiah Florist Manna Shop, South Bengkulu Regency. The value of the coefficient of determination from the calculation results using SPSS can be seen as the coefficient of determination value of the R square of 0.733. This means that the value of social media marketing (X1), the value of brand image (X2), influences the purchasing decision (Y) by 73.3%, while the remaining 26.7% is influenced by other variables that were not examined in this study.